2003
DOI: 10.1097/00008571-200308000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in mitochondrial aldehyde dehydrogenase (ALDH2) change cofactor affinity and segregate with voluntary alcohol consumption in rats

Abstract: Genetic factors influence alcohol consumption and alcoholism. A number of groups have bred alcohol drinker and non drinker rat strains, but genetic determinants remain unknown. The University of Chile rat lines UChA (low drinkers) and UChB (high drinkers) display differences in the relative K(m) for NAD+ of mitochondrial aldehyde dehydrogenase (ALDH2) but no V(max) differences. The relative K(m) differences may be due to mitochondrial changes or to genetic differences coding for ALDH2. We investigated whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Thus, Aldh2 2 and Aldh2 3 are specific for low and high drinkers, respectively, in these lines. The Aldh2 3 allele codes for arginine-67 but also contains a second point mutation that changes glutamic-479 into lysine-479 (17). These point mutations in rat Aldh2 are different from those in human ALDH2 (Glu-487 into Lys-487) (18,19).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, Aldh2 2 and Aldh2 3 are specific for low and high drinkers, respectively, in these lines. The Aldh2 3 allele codes for arginine-67 but also contains a second point mutation that changes glutamic-479 into lysine-479 (17). These point mutations in rat Aldh2 are different from those in human ALDH2 (Glu-487 into Lys-487) (18,19).…”
mentioning
confidence: 98%
“…Recently, a mutation in the Aldh2 gene (lower case nomenclature used for rodents) was shown to strongly segregate with voluntary ethanol consumption in Wistar-derived rats (17). Low alcohol-consuming (UChA) rats display a point mutation in the Aldh2 gene that changes glutamine-67 (Aldh2 1 allele) into arginine-67 (Aldh2 2 allele) in the enzyme coded.…”
mentioning
confidence: 99%
“…Rats of the UChA line (virtually Abstainer) display a mutation in the aldh2 gene (Sapag et al, 2003; see Quintanilla et al, 2006), which codes for an enzyme with a higher K m for NAD + and a lower Vmax that the ALDH2 of heavy drinker animals (UChB; Bibulous). Further, the levels of arterial acetaldehyde display a large “acetaldehyde burst,” reaching 40–50 μM (vs. 10–20 μM for controls), which deters their alcohol intake (Quintanilla et al, 2005b).…”
Section: Aversive Effects Of Liver-generated Acetaldehydementioning
confidence: 99%
“…The mechanisms leading to alcohol rejection in the virtually abstainer UChA line are mainly related to polymorphisms in nuclear and mitochondrial genes that lead to a slow metabolism of acetaldehyde and to high blood acetaldehyde levels. These UChA studies have been previously described (Sapag et al, 2003; Quintanilla et al, 2005, 2006; Israel et al, 2013) and thus not covered in the present review. Studies conducted in UChB rats are indicated in the text.…”
Section: Introductionmentioning
confidence: 98%